2005
DOI: 10.1016/j.bbrc.2005.06.065
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor impairs the functional ability of dendritic cells through Id pathways

Abstract: Vascular endothelial growth factor (VEGF) is an angiogenic cytokine that plays an important role in tumor growth and progression. Recent evidence suggests an alternate, albeit indirect, role of VEGF on host immune response to tumors. VEGF appears to diminish host immunity by altering the function of major antigen-presenting cells such as dendritic cells (DCs) [D.I. Gabrilovich, T. Ishida, S. Nadaf, J.E. Ohm, D.P. Carbone, Antibodies to vascular endothelial growth factor enhance the efficacy of cancer immunothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 22 publications
0
70
0
Order By: Relevance
“…However, in our in vitro incubation system of human leukocytes, we cannot rule out the possibility that coexisted iMC might have inhibited the maturation of DC during overnight incubation time. By using in vitro culture system of murine cells, Dikov et al [17] and Laxmanan et al [33] reported the direct impairment of DC function by VEGF is mediated primarily by VEGFR1/Flt-1. Dikov reported that VEGF acted on early stage of DC differentiation but not later phase of maturation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our in vitro incubation system of human leukocytes, we cannot rule out the possibility that coexisted iMC might have inhibited the maturation of DC during overnight incubation time. By using in vitro culture system of murine cells, Dikov et al [17] and Laxmanan et al [33] reported the direct impairment of DC function by VEGF is mediated primarily by VEGFR1/Flt-1. Dikov reported that VEGF acted on early stage of DC differentiation but not later phase of maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, murine models have indicated that VEGF inhibition may be a means of overcoming immune resistance 42,43 and, thus, may enhance the IL-2 antitumor effect that potentially is increased by LEN.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of VEGF during culture, DC from wild-type mice displayed an inhibition of antigen presentation capacity, which was not observed for DC from Id1 −/− mice under the same experimental settings. Furthermore, addition of neutralizing anti-Flt-1 antibody abrogated the inhibitory effect of VEGF on wild-type DCs (Laxmanan, et al 2005). …”
Section: Cytokines/chemokinesmentioning
confidence: 99%